Free estradiol index levels associated with high sensitivity CRP levels in male children - Ağırbaşlı, Mehmet; Tanrıkulu, Azra; Azizy, Munir (The Turkish Journal of Pediatrics, 2017)
Biomarkers of inflammation such as high-sensitivity C-reactive protein (hs-CRP) associate with subclinical atherosclerosis. Atherosclerosis is an early onset disease in life. Sex hormones and puberty modulate metabolism in children. Studies indicate that low sex hormone binding globulin (SHBG) levels associate with insulin resistance and metabolic syndrome in children. The aim of this study is to study the correlation between sex hormones and hs-CRP levels in children and adolescents. The study sample was derived from a cross sectional survey on the prevalence of cardiovascular risk factors in a representative sample of school children (8-17 year-old) in Istanbul, Turkey. In addition to anthropometric and biochemical characteristics of cardiovascular risk, sex hormones such as free androgen index, free estradiol index (FEI), SHBG and hs-CRP levels were measured in all study participants: 91 boys (12.4 ± 3.4 years) and 77 girls (12.7 ± 3.4 years) were included in the study. Median (interquartile range) hs-CRP levels were similar among boys and girls [0.36 (0.9) versus 0.45 (0.7) mg/dl, p= 0.725]. Gender stratified analysis displayed that hs-CRP levels positively correlated with FEI levels (r=0.438, p < 0.001) in boys. Linear regression analysis was performed to determine the predictors of hs-CRP. Among covariates of FEI, homeostasis model assessment-estimated insulin resistance, body mass index, age, and SHBG; FEI was shown to significantly and independently predict hs-CRP levels in boys [β=2.758, p < 0.001, 95% confidence interval (CI) for β 1.471-4.045]. FEI levels associate with subclinical inflammation in boys. Future studies may elucidate the role of sex hormone levels in inflammation among children.